Perubahan Karakteristik Pangan Tradisional Pesan Tlengis Selama Penyimpanan Suhu Ruang - Bhaskara, Desak Nyoman Anggreni; Trisna Darmayanti, Luh Putu; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
Pesan tlengis is one of Balinese foods made from tlengis or blondo, which is a waste from the process of producing coconut oil in the form of white sediment. In general, the process of producing pesan tlengis is that the tlengis was added with basa genep (complete seasoning), wrapped in banana leaves, and then roasted. Pesan Tlengis was damaged when stored at room temperature of 25oC-30oC, with storage time above 12 hours. Pesan tlengis was damaged during storage at room temperature due to the high content of nutrients such as fat, protein, and water. The high nutrient content in pesan tlengis can be reduced by adding a steaming process. This study was aimed to determine the changes in the characteristics of pesan tlengis during storage at room temperature and to find out how long pesan tlengis can still be consumed during storage at room temperature. This study used a completely randomized design (CRD) with storage time treatment consisting of 4 levels, namely T0 (0 hours), T1 (24 hours), T2 (48 hours), and T3 (72 hours). The data obtained were analyzed by analysis of variance (ANOVA) and if there was a significant effect between treatment levels, it was followed with Duncan's Multiple Range Test. The results showed that the storage time of pesan tlengis at room temperature had a significant effect on moisture content, ash content, protein content, fat content, carbohydrate content, total microbial plate, total mold and yeast, total coliform, texture and aroma. Storage time of 24 hours was the period of time when pesan tlengis can still be consumed with a moisture content value of 5.40%, ash content 3.13%, protein content 12.2%, fat content 55.08%, carbohydrate content 24.71%, total microbial plate 5.99 log cfu / ml, total mold and yeast 0 log cfu / ml, negative coliform, ordorless sour aroma , and the texture slightly slimy.